2011
DOI: 10.1371/journal.pone.0027563
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Independent Transmission of Transgenic Fluorophore Protein by Boar Spermatozoa

Abstract: Recently, we generated transposon-transgenic boars (Sus scrofa), which carry three monomeric copies of a fluorophore marker gene. Amazingly, a ubiquitous fluorophore expression in somatic, as well as in germ cells was found. Here, we characterized the prominent fluorophore load in mature spermatozoa of these animals. Sperm samples were analyzed for general fertility parameters, sorted according to X and Y chromosome-bearing sperm fractions, assessed for potential detrimental effects of the reporter, and used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Transposase-catalyzed DNA integration seems to favor transcriptionally permissive loci, and all transgenic pigs we have examined, from the founder to the F2 generation showed the expected expression patterns 42,48 . Thus, transposition-mediated transgenesis compares favorably to current alternatives, particularly if the overall success rates of 6-8 % (ratio of transgenic animals with desired phenotype per treated zygotes) and the success rates of 40-60 % of transgenic founders per born animals are taken into account.…”
Section: Transgenesis Using the Sleeping Beauty Transposonmentioning
confidence: 87%
See 1 more Smart Citation
“…Transposase-catalyzed DNA integration seems to favor transcriptionally permissive loci, and all transgenic pigs we have examined, from the founder to the F2 generation showed the expected expression patterns 42,48 . Thus, transposition-mediated transgenesis compares favorably to current alternatives, particularly if the overall success rates of 6-8 % (ratio of transgenic animals with desired phenotype per treated zygotes) and the success rates of 40-60 % of transgenic founders per born animals are taken into account.…”
Section: Transgenesis Using the Sleeping Beauty Transposonmentioning
confidence: 87%
“…One useful way to detect transgene integration and expression is to employ a fluorescent reporter protein, such as Venus, which is an optimized (brighter) derivative of the enhanced yellow fluorescent protein (EYFP). We have previously demonstrated that an SB transposon carrying a CAGGS (CMV enhancer, chicken beta actin promoter)-driven Venus transgene (pT2-RMCE-Venus) facilitates the detection of transgenic animals 38,39,48 .…”
Section: Experimental Designmentioning
confidence: 99%
“…Recently, the generation of transgenic pigs with systemic expression of vital fluorophore markers has found widespread interest (311), e.g., for improving gene transfer technologies in pigs (3,5,79,11), for transplantation studies (4,10), for testing the functionality of multicistronic transgene constructs (2), and for visualizing epigenetic phenomena during spermatogenesis and fertilization (6). …”
mentioning
confidence: 99%
“…A litter of 8 cloned piglets was genotyped by standard blotting procedures. According to the restriction of genomic DNA, an internal fragment of 1.4 kb (arrow) and an external fragment (asterisk) of > 3 kb are predictive for hemizygous cloned animals carrying a monomeric integration [for details see (6)]. 1, carrier sow (non-transgenic); 29, cloned piglets; 10, empty; 11, non-related wildtype animal; 12, empty; M, positive control (with bands of 1.4 and 4.9 kb).…”
mentioning
confidence: 99%
“…So far only few studies assessed the toxicity of NP on spermatozoa of farm animals. The recent development of transgenic pigs with fluorophore-loaded spermatozoa (Garrels et al 2011) may be instrumental for establishment of direct comparative tests.…”
Section: R18 D Rath and Othersmentioning
confidence: 99%